STUDIES ON FROZEN STORAGE OF MINCED FISH FROM THREADFIN BREAM - JOSEPH, JOSE; PERIGREEN, P A (Fishery Technology, 2017)
Minced fish prepared from threadfin bream ( Nemipterus japonicus) was frozen asblocks, packed in polythene lined waxed cartons and stored at - 23Â°C. The changestaking place during storage were followed. There was good correlation between theorganoleptic quality, extractability of protein, cook drip loss and weight loss on thawing. The frozen minced fish was acceptable upto 28 weeks under frozen storage.